Assessment of Surface Water Quality Status Using the Pollution Index Method in Tukad Badung River - Kadek Diana Harmayani; Ni Made Pertiwi Jaya; Ida Ayu Rai Widhiawati; I Gede Andy Andika Parahita; Ngakan Gede Agung Khrisna Wiryananda; Ni Nyoman Dewi Supriyani; I Gusti Agung Gede Wiranata Baskhara; Debora Sofia Fransiska Hutagalung; Daniel Rizal Mahendra (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
This research proposes to find out the present state of the water's purity in Tukad Badung through an examination of the Pollution Index (PI) adopted from the methodology presented by the Water Quality Index (WQI), which was presented by the Indonesian Ministry of Environment. A series of water samples were taken at three river flow points in the Denpasar City area, representing the upstream, middle, and downstream areas. The water quality parameters were determined based on the characteristics of domestic wastewater pollutant sources that are identified in watershed areas. In accordance with Regulation 22 of the Government of 2021 concerning quality standards for river water used for drinking water, the average concentrations of Total Suspended Solid (TSS), Ammonia, Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) parameters have exceeded quality standards. Meanwhile, the oil and grease parameter, as well as detergents, still meet quality standards. The PI at three monitoring points was obtained at 2.41 – 4.27, categorized as lightly polluted. In the future, efforts to deal with water pollution are critical to meet the downstream water quality standards used as drinking water.